Recommendations for the selection of parameters for shunting locomotives - Kuznetsov, Valeriy; Liubarskyi, Borys; Kardas-Cinal, Ewa; Yeritsyan, Bagish; Riabov, Ievgen; Rubanik, Ivan (Warsaw University of Technology, 2020)
Shunting is an integral part of the partial process. In 1520 mm gauge countries, shunting operations are performed by outdated locomotives, which are being replaced by modern models; the technical parameters best match the conditions of the shunting work performed. The article analyzes recommendations for the selection of parameters of shunting locomotives and the actual indicators of their work. On the basis of this analysis, a requirement was made on the necessity of compulsory consideration of the operating conditions of the locomotive when determining its technical characteristics. As the main technical parameters of shunting locomotives, the tractive power and starting tractive force are taken and their influence on the duration of an elementary shunting movement of the "acceleration-deceleration" type is investigated. This approach advises the regulatory documentation for the organization of shunting work. Tha developed mathematical model allows to carry out research on the influence of tractive power and starting tractive force on the time of acceleration and deceleration. Calculations of the time of the train's acceleration are carried out with varying their mass and the slope of the track at different values of the tractive power starting tractive force. The calculations were carried out for the mass of compositions 1000...5000 Mg for the profile slopes equal to 0 and 1.5 ‰. The speed of the finish of acceleration was taken equal to 15 and 25 km/h. The thrust starting tractive force varied in the range of 150...300 kN, the tractive power - 200 ... 1100 kW. According to the results of calculations, it was found that the reduction in the duration of the elementary shunting movement is more significantly affected by the power of the locomotive than by the starting traction force. The “saturation” effect was noted, in which a significant increase in power or traction force during starting does not cause a significant reduction in the acceleration time. In this regard, for shunting locomotives with AC traction drive, it is recommended to take a pulling force of an equal continuous traction force.
Keywords: shunting locomotive; starting traction force; tractive power at the wheel; elementary shunting movement